(λ^2)xe^-λx原函数
(λ^2)xe^-λx原函数
∫xe^(x^2)dx=( ) A: 1/2(e^(x^2)) B: 1/2(e^(x^2))+C C: -1/2(e^(x^2)) D: -1/2(e^(x^2))十C
∫xe^(x^2)dx=( ) A: 1/2(e^(x^2)) B: 1/2(e^(x^2))+C C: -1/2(e^(x^2)) D: -1/2(e^(x^2))十C
曲线y=xe^1/(x^2)的渐近线是?
曲线y=xe^1/(x^2)的渐近线是?
求y=xe^(2/x)+1的斜渐近线
求y=xe^(2/x)+1的斜渐近线
y=xe^x^2(x乘以e^x的二次方)在x=0处的微分
y=xe^x^2(x乘以e^x的二次方)在x=0处的微分
曲线y=xe^x拐点的横坐标为()。 A: 2 B: 1 C: -1 D: -2
曲线y=xe^x拐点的横坐标为()。 A: 2 B: 1 C: -1 D: -2
已知x+y-z=e<sup>x</sup>,xe<sup>x</sup>=tant,y=cost,则(dz/dt)|<sub>t</sub><sub>=0</sub>=()。 A: 1/2 B: -1/2 C: 1 D: 0
已知x+y-z=e<sup>x</sup>,xe<sup>x</sup>=tant,y=cost,则(dz/dt)|<sub>t</sub><sub>=0</sub>=()。 A: 1/2 B: -1/2 C: 1 D: 0
设\(z = \int_ { { x^2}}^y { { e^t}\sin t} dt\),则\({z_{xx}=}\) A: \(2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} + 2{x^2}\cos {x^2}} \right]\) B: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} - 2{x^2}\cos {x^2}} \right]\) C: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} + 2{x^2}\cos {x^2}} \right]\) D: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\cos {x^2} + 2{x^2}\sin {x^2}} \right]\)
设\(z = \int_ { { x^2}}^y { { e^t}\sin t} dt\),则\({z_{xx}=}\) A: \(2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} + 2{x^2}\cos {x^2}} \right]\) B: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} - 2{x^2}\cos {x^2}} \right]\) C: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} + 2{x^2}\cos {x^2}} \right]\) D: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\cos {x^2} + 2{x^2}\sin {x^2}} \right]\)
设函数,则Q′(x)等于:() A: xe B: -xe C: D: -
设函数,则Q′(x)等于:() A: xe B: -xe C: D: -
求不定积分[img=132x48]17da6537fc8dad6.png[/img]; ( ) A: -(4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) B: (4*(sin(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) C: (4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) D: (4*(cos(x/2)/2 + 2*cos(x/2)))/(17*exp(2*x))
求不定积分[img=132x48]17da6537fc8dad6.png[/img]; ( ) A: -(4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) B: (4*(sin(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) C: (4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) D: (4*(cos(x/2)/2 + 2*cos(x/2)))/(17*exp(2*x))